Posthumous assisted reproduction policies among a cohort of United States' in vitro fertilization clinics - Emma Trawick, M.D; Amani Sampson, B.A; Kara Goldman, M.D; Lisa Campo-Engelstein, Ph.D; Arthur Caplan, Ph.D; David L. Keefe, M.D; Gwendolyn P. Quinn, Ph.D (Elsevier, 2020)
Objective: To assess the presence and content of policies toward posthumous assisted reproduction (PAR) using oocytes and embryos among Society for Assisted Reproductive Technology (SART) member clinics in the United States. Design: Cross-sectional questionnaire-based study. Setting: Not applicable. Patient(s): A total of 62 SART member clinics. Intervention(s): Questionnaire including multiple choice and open-ended questions. Main Outcome Measure(s): Descriptive statistics regarding presence and content of policies regarding PAR using oocytes and embryos, consent document content regarding oocyte and embryo disposition, and eligibility of minors and those with terminal illness for fertility preservation. Result(s): Of the 332 clinics contacted, 62 responded (response rate 18.7%). Respondents were distributed across the United States, and average volume of in vitro fertilization (IVF) cycles per year ranged from <250 to >1,500, but 71.2% (n = 42) reported a volume of <500. Nearly one-half (42.4%, n = 25) of clinics surveyed reported participating in any cases of posthumous reproduction during the past 5 years, and 6.8% (n = 4) reported participation in >5 cases. Participation in cases of posthumous reproduction was not significantly associated with practice type or IVF cycle volume among those surveyed. Only 59.6% (n = 34) of clinics surveyed had written policies regarding PAR using oocytes or embryos, whereas 36.8% (n = 21) reported they did not have a policy. Practice type, IVF cycle volume, fertility preservation volume, and prior participation in cases of PAR were not significantly associated with the presence of a policy among respondent clinics. Of those with a policy, 55.9% (n = 19) reported they had used that policy, 59.1% (n = 13) without a policy reported they had considered adopting one, and 63.6% (n = 14) reported they had received a request for PAR services. Only 47.2% (n = 25) of clinics surveyed specified that patients not expected to survive to use oocytes due to terminal illness are eligible for oocyte cryopreservation, whereas 45.3% (n = 24) did not specify. Conclusion(s): Respondent clinics reported receiving an increasing number of requests for PAR services, but many also lacked PAR policies. Those with policies did not always follow ASRM recommendations. Given the low response rate, these data cannot be interpreted as representative of SART clinics overall. As PAR cases become more common, however, this study highlights poor reporting of PAR and institutional policies toward PAR, suggesting that SART clinics may not be equipped to systematically manage the complexities of PAR.